PENGEMBANGAN LEMBAR KERJA SISWA MATEMATIKA BERBASIS PENEMUAN TERBIMBING UNTUK SISWA KELAS VIII SMP MATERI LINGKARAN - Sitorus, Rospiala (Universitas Pasir Pengaraian, 2016)
This study aims to generate math worksheets based discovery Guided valid and practical in the material Circle. This type of research was the development of research (Research and Development), which consists of three stages of development of the definition (Define), the design (Design) and development (Develop). The subjects were students of class VIII SMPN 5 Rambah Samo in the first semester of the school year 2015/2016. The instrument used in this study was a validation questionnaire sheet and questionnaire sheet practicalities. Results of this research-based LKS Guided discovery. Based on test validity based LKS Guided discovery that has been made to four people validator with some revisions and corrections then obtained an average score of validation results based LKS Guided discovery was Â 3.05 with a valid category. Based on the practicalities of the test by using a questionnaire, observation of the implementation of learning the importance of the expert scores 82% with a practical category, teachers 85% categorized as very practical and students 85% categorized as very practical. So it can be concluded that based LKS Guided discovery was valid and practical. PENGEMBANGAN LEMBAR KERJA SISWA Â MATEMATIKABERBASISPENEMUAN TERBIMBING UNTUK Â SISWA KELAS VIIISMP MATERI LINGKARAN